Assessing the Impact of Organizational Climate, Human Resources Quality, Work Ethos, and Job Satisfaction on Employee Performance - Kinasih, Wiwit (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2022)
The company has human resources that have a high level of competence, so several problems within the company must be prevented and resolved by the company, one of which is the performance of employees within the company. With this research it is intended to obtain or collect data and then process it into information about the influence of organizational climate, quality of human resources, work ethic, and job satisfaction on employee performance. To answer the following objectives, a quantitative scientific method is needed, with a sample of 95 employees. The data analysis method used in conducting this research is instrument test, classical assumption test and linear regression analysis. So the results obtained in this study are that there is a significant influence of organizational climate, quality of human resources, work ethic, and job satisfaction simultaneously on employee performance.